Assessing the information quality of phishing-related content on financial institutions' websites. (12th November 2018) - Butler, Rika; Butler, Martin
Abstract : Purpose: Phishing attacks exploit social vulnerabilities and remain a global concern. Financial institutions often use their websites as part of their online awareness and education efforts. This paper aims to explore the effectiveness of phishing-related information made available by financial institutions to raise awareness and educate customers. Design/methodology/approach: In this mixed methods research, a survey of online consumers was first performed and analysed. Second, the information available on the websites of major financial institutions was analysed. Using the construct of information quality (IQ), content analysis was performed to determine whether the phishing-related information meets the IQ criteria. Findings: The survey confirmed that consumers are indeed targeted by phishers. It established that they turn to their financial institutions, more often than any other source, for anti-phishing information. When analysing the IQ of phishing-related information, significant deficiencies as well as different levels of performance between the financial institutions, emerged. In general, the worst performing IQ criteria was information being current and fit for purpose. Research limitations/implications: As the research is conducted within South Africa, the results cannot be generalised. The ethical clearance did not allow for identification of the different financial institutions and thus comparing consumers' perceptions with the observed IQ from the content analysis to determine correlation. Practical implications: Protecting consumers against phishing attacks remains critical, and this paper confirms that users turn to their financial institutions for information. Yet, the phishing-related information made available on the websites of financial institutions has severe deficiencies. Practitioners should use IQ to determine the appropriateness of phishing-related information and focus on improving customer awareness and education. Originality/value: Researchers often highlight the importance of awareness and education programmes in protecting consumers, but rarely investigate if consumers access publicly available information and express an opinion on the quality of this information. Although the results should not generalised, the recommendations, if necessary through similar analysis, has an impact beyond the geographical constraints of the study.